2017
DOI: 10.1111/josi.12204
|View full text |Cite|
|
Sign up to set email alerts
|

“Fear of Falling”: Economic Instability Enhances Collective Angst among Societies’ Wealthy Class

Abstract: In 2008, an era of unprecedented growth and prosperity came to an end, and the world was plunged into the Great Recession, a Global Financial Crisis (GFC)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 35 publications
6
92
2
3
Order By: Relevance
“…A similar result applied to the ingroup (Jetten et al., ): the wealthier the group, the more participants inferred it was competent and capable. However, the warmest group was the moderately wealthy group, with both the “rich” and the “poor” group as colder.…”
Section: Social Class the Great Recession And Social Psychology: Thmentioning
confidence: 59%
“…A similar result applied to the ingroup (Jetten et al., ): the wealthier the group, the more participants inferred it was competent and capable. However, the warmest group was the moderately wealthy group, with both the “rich” and the “poor” group as colder.…”
Section: Social Class the Great Recession And Social Psychology: Thmentioning
confidence: 59%
“…Although the effects economic crises have on hostile ethnocentrism appear in much previous research (e.g., Doty et al., ), we for the first time tested a group‐based control account that may help to identify underlying processes (i.e., threatened control) and to tailor effective interventions. This account fits opposition to immigration among wealthy populations who experience threat to economic stability and presumably the ability to control it (Jetten, Mols, Healy, Spears, & Postmes, ).…”
Section: Discussionmentioning
confidence: 82%
“…Research reported by Jetten, Mols, Healy, and Spears () is also relevant to this issue. These authors examined how economic instability affects low‐SES and high‐SES people.…”
Section: Social Cognition and Attitudesmentioning
confidence: 88%